PENERAPAN COMMUNITY BASED TOURISM (CBT) DI DESA MERAK BELANTUNG KABUPATEN LAMPUNG SELATAN DALAM MEWUJUDKAN DESA EKOWISATA - Yulianto Yulianto; Selvi Diana Meilinda; Teuku Fahmi; Dewi Ayu Hidayati; Astiwi Inayah (Jurnal Abdi Insani, 2022)
Merak Belantung Village is one of the villages in Kalianda District, South Lampung Regency which has a variety of tourism potential. However, the current tourism potential of the village has not been optimally utilized by the local community. For this reason, efforts to realize an ecotourism village in Merak Belantung require assistance from academics by involving village community organizations. This is in line with the development of ecotourism villages based on community based tourism (CBT) which emphasizes the involvement of local community participation. This community service activity aims to increase the capacity of local communities in realizing ecotourism village destinations in Merak Belantung. The method of activities carried out includes socialization, counseling, mentoring, to providing equipment for pokdarwis. The socialization and counseling activities were attended by around 34 people consisting of elements of village apparatus and pokdarwis managers. Service activities by focusing on efforts to develop CBT-based ecotourism villages were carried out for the first time in Merak Belantung Village. The service participants looked enthusiastic and actively involved in every series of activities organized by the PkM team. During the outreach and socialization activities, the participants provided a lot of information about the tourism potential of their village. For this reason, the results of this service activity have also mapped the potential of Merak Belantung Village referring to the SWOT analysis and 7 Landscape Analysis. In addition, there is a high commitment among village officials and pokdarwis managers to focus on developing ecotourism villages in Merak Belantung. This service activity brings new understanding in efforts to develop ecotourism villages, especially the application of the CBT concept. For this reason, sustainable assistance is needed in realizing ecotourism village destinations in Merak Belantung Village.